The Impact of Animal Models and Strain Standardization on the Evaluation of Tuberculosis Vaccine Efficacy - Jiazheng Wei; Junli Li; Xiaochi Li; Weixin Du; Cheng Su; Xiaobing Sheng; Yang Huang; Jinsong Wang; Qun Niu; Guoqing Chen; Wei Tian; Aihua Zhao; et al. (Vaccines)
Tuberculosis (TB) remains one of the most significant challenges to global public health. Vaccine development is a critical strategy for the prevention and control of TB. However, evaluating the protective efficacy of TB vaccines faces numerous challenges, particularly in the selection of animal models and bacterial strains. Variations in animal models, challenge strains, challenge routes, and doses can significantly impact the outcomes of preclinical evaluations. This article highlights the importance of standardizing preclinical evaluation models, summarizes the animal models and challenge strains used in novel TB vaccine candidates, efficacy studies, and discusses the advantages and limitations of commonly used animal models in TB vaccine research. It also points out the differential performance of various animal models in simulating protection and pathology. Given the current limitations of using a narrow range of challenge strains and the lack of standardized infection routes and doses, this article calls for the establishment of more standardized challenge strains and the development of standardized evaluation models to improve the reliability and generalizability of new TB vaccine efficacy assessments.